PENGARUH PENAMBAHAN GAS HHO TERHADAP UNJUK KERJA MOTOR YAMAHA R15 BAHAN BAKAR PERTALITE dan PERTAMAX - Sarjono Sarjono (UNIVERSITAS ISLAM MALANG, 2021)
The demand for fuel oil (BBM) continues to increase, considering that until now oil is the main source of national energy. Especially in the automotive world, which still depends on its energy consumption on fuel. The most energy demand in the transportation sector is fuel (96%) in 2018 and the rest is supplied by biodiesel and natural gas. The conversion of oil-fueled vehicles to electricity and gas has not been able to shift the dominance of fuel-based transportation technology, but currently there is a lot of research on water fuel (blue energy) which is used as an additional fuel for motor fuel. Brown's Gas is a gas produced by the process of breaking pure water (H2O) by electrolysis. The gas produced from the water electrolysis process is Hydrogen and Oxygen gas, with a composition of 2 Hydrogen and 1 Oxygen (HHO). (Lowrie, P.E.W., 2005). The addition of HHO gas to a vehicle is one way to mix hydrogen gas (H2) and oxygen gas (O2) into fuel. The HHO (Brown gas) supply system works on the principle of the water electrolysis cell. This cell consists of a pair of electrodes immersed in an electrolyte solution (water) and supplied with electrical power from the vehicle battery. As a result, hydrogen gas (H2) and oxygen gas (O2) electrodes are formed. This gas is then used to increase the air content in the engine (combustion chamber) of the vehicle. There are many studies that discuss the effect of HHO gas on the performance of the combustion motor, for this reason, this study will examine the effect of adding hydrogen gas (HHO) on the performance of Pertamax and pertalite fuels. Testing on HHO gas production with a 10% catalyst from 500 ml of distilled water with a power source from a 12 V 5A battery Consumption of 60 watts of electric power used, can produce HHO gas of 16.7 ml / s, with a generator efficiency of 68, 83% . The results of the comparison of the four types of fuel obtained the optimal torque value of 16.7 Nm at 8000 rpm using pertalite fuel. The results of the comparison of the four types of fuel obtained the optimal power value of 9.79 HP at 8000 rpm. Using Pertamax fuel with HHO gas.